“Famílias”, ascensão social e alinhamentos partidários no rio grande do sul - Grill, Igor Gastal (2014)
The present research examines the dynamics and development of a political heritage frame and the ways and means by which it is trasmitted and assumed by agents belonging to political families and parties. The study dimensions privileged in this paper encompass strategies employed by agents acting for the appreciation and “recovery” of the various “political traditions” of Rio Grande do Sul, the reproduction of political capital, the celebration of their “founders”, and the management of their memory and “legacy”. Special emphasis was given to practices, codes, mechanisms and instruments for the presentation and celebration of the “political families”.